Trained immunity inducers in cancer immunotherapy - Sui, Yongjun; Berzofsky, Jay A. (Frontiers in Immunology, 2024)
While most of the cancer immunotherapy strategies engage adaptive immunity, especially tumorassociated T cells, the small fraction of responding patients and types of cancers amenable, and the possibility of severe adverse effects limit its usage. More effective and general interventions are urgently needed. Recently, a de facto innate immune memory, termed 'trained immunity', has become a new research focal point, and promises to be a powerful tool for achieving long-term therapeutic benefits against cancers. Trained immunity-inducing agents such as BCG and fungal glucan have been shown to be able to avert the suppressive tumor microenvironment (TME), enhance T cell responses, and eventually lead to tumor regression. Here, we review the current understating of trained immunity induction and highlight the critical roles of emergency granulopoiesis, interferon  and tissue-specific induction. Preclinical and clinical studies that have exploited trained immunity inducers for cancer immunotherapy are summarized, and repurposed trained immunity inducers from other fields are proposed. We also outline the challenges and opportunities for trained immunity in future cancer immunotherapies. We envisage that more effective cancer vaccines will combine the induction of trained immunity with T cell therapies.